Improving Management Effectiveness through Personality and Emotional Analysis: A Study on Parsingguran II Tourism Village - Sinulingga, Samerdanta; Lubis , Andi Pratama; Ayuningtias , Niza; Siregar , Ronald Leonardo; Pardosi, Jhonson; Marpaung, Jonathan Liviera (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study aims to improve management effectiveness in the Parsingguran II Tourism Village by analyzing key personality and emotional dimensions of managers. Using data and Structural Equation Modeling (SEM) via SmartPLS, we examine how personality traits such as Dominance, Social Recognition, and Achievement Drive influence emotional dimensions like Emotional Stability, Empathy, and Self-Regulation. These emotional dimensions, in turn, impact management effectiveness. The analysis reveals significant indirect effects of personality traits on management outcomes through emotional pathways. Sensitivity analysis demonstrates that small changes in personality dimensions can significantly affect management effectiveness. Based on these findings, we propose strategies for enhancing management effectiveness by developing leadership, communication, emotional intelligence, and operational processes. The insights gained from this research provide a valuable framework for tourism villages and similar organizations to enhance their managerial practices through targeted personality and emotional interventions.